Implementasi Metode Economic Order Quantity (EOQ) Terhadap Persediaan Local Nut Weld M10-OI di PT. ECP - Adimas Ristansyah, Ferry; Momon S., Ade (Fakultas Teknik Universitas Tulang Bawang, 2025)
PT. ECP is a manufacturing company that produces excavator components. The problems experienced by PT. ECP is the occurrence of inventory that exceeds capacity. The excess capacity was due to the continuous purchase of Local Nut Weld M10-OI every month plus the remaining raw materials from the previous period. This study aims to apply the EOQ method to the inventory system of PT. ECP to minimize the problem of excess inventory. The results obtained from the application of the EOQ method are the number of each order of 30,742 units with a safety stock of 482 units and the frequency of orders every 2 months. Reorders are made when the remaining inventory is 3,615 units, the maximum inventory is 31,224 units, and the total inventory cost is Rp. 384,274 with a difference of Rp. 89,170 when compared to the cost of inventory before applying the EOQ method. Keywords: EOQ, Inventory, Reorder Point, Safety Stock, Total Inventory Cost